The Legal Aspects Fulfillment of Tax Responsibilities for Micro and Small Enterprises Established as Individual Company - Rachman, Aditya; Sudaryat, Sudaryat; Cahyadini, Amelia (JUSTISI, 2024)
An Individual Company is a new legal entity intended for Micro and Small Enterprise (MSE) actors to obtain legal entity status. However, based on the taxation perspective, establishing an Individual Company raises the consequence of tax imposition on one party that is substantially the same entity, namely MSEs as Individuals and Individual Companies as Legal Entities. This study intends to examine the taxation responsibility attached to the Individual Company as a law entity so taxpayers can carry out their tax obligations. The study method used is normative juridical with descriptive-analytical research specifications and qualitative juridical data analysis. The results of this study indicate that MSE actors who establish themselves as Individual Companies are given Corporate Taxpayer status with all its legal consequences. Direktorat Jenderal Pajak (DJP) needs to make adjustments and relax the Rights and Obligations of Corporate Taxpayers in the form of Individual Companies so that the tax self-assessment system is still implemented effectively, easily, and efficiently for taxpayers so that it has an impact on legal certainty and increases the level of taxpayer compliance.